A Systematic Review of the Efficacy of Corticosteroid Injections of Tendon Sheaths, Excluding Stenosing Tenosynovitis of the Wrist and Hand. (July 2021) - Cushman, Daniel M.; Carefoot, Andrea; Lisenby, Suzan; Caragea, Marc; Fogg, Benjamin; Conger, Aaron
Abstract : Objective: Corticosteroid injections into tendon sheaths are common in clinical practice for treatment of a variety of tendon disorders. Previous systematic reviews have been performed on injections for stenosing tenosynovitis (DeQuervain tenosynovitis and trigger finger), but little high-level evidence remains for other tendon sheath injections. This systematic review analyzes the available literature on improvements in pain and function after these injections. Design: This systematic review of MEDLINE and Embase databases, as well as article bibliographies, examined studies of adult tendon sheath injections, excluding DeQuervain and trigger finger injections. Studies with and without comparison groups were examined. Risk of bias assessment was additionally performed. Results: Abstracts from 1293 records were screened, and 187 full-text articles were reviewed. Seven articles met final inclusion criteria, of which five were prospective trials and none were compared with a placebo. The proximal biceps, peroneal, finger flexor, and posterior tibialis tendons were explicitly examined. All articles reported at least short-term improvements in pain, and some reported improvement in function. Conclusions: Low-quality studies exist that suggest tendon sheath injections may provide at least short-term improvement in pain. Controlled studies are required to fully demonstrate efficacy. Abstract : Supplemental digital content is available in the text.